A micro-nano texture anti-reflection structure for solar cells and preparation method thereof
The formation of micron or nanoscale trapped light structures on the solar cell by soft nanoimprinting method solves the problems of silicon wafer loss and waste liquid treatment in the preparation of traditional anti-reflection structures, and significantly improves the photoelectric conversion efficiency and battery performance of the solar cell.
Patent Information
- Application Number
- CN202310125363.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-16
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-02-16
AI Technical Summary
In the anti-reflection structure preparation process of existing solar cells, corrosion of alkali or acid liquid leads to silicon wafer loss and waste liquid treatment cost, and the trapped light structure is difficult to form uniformly on the polysilicon surface, affecting battery performance.
Using soft nanoimprinting method to form micro- or nano-scale trap light structures on the flat anti-reflection film of solar cells, polyurethane materials and hard template transfer technology are used to prepare textured anti-reflection layers of various morphology to replace traditional alkali Liquid or acid etching method.
It achieves significant anti-reflection effect in a wide band, improves the photoelectric conversion efficiency of solar cells, reduces production costs, and is environmentally friendly and simple, compatible with existing battery preparation processes.
Smart Images

Figure CN116314357B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solar cells, and in particular relates to a micro-nano texture anti-reflection structure for solar cells and a preparation method thereof. Background Art
[0002] Solar cells can directly convert light energy into electrical energy based on the photovoltaic effect. With the continuous advancement of technology, the cost of electricity has gradually decreased, and the photovoltaic industry has developed vigorously in recent years. At present, in the photovoltaic industry, crystalline silicon solar cells still account for more than 90% of the market share, while thin-film solar cells are also developing rapidly, such as amorphous silicon, perovskite, copper indium gallium selenide, cadmium telluride, etc., which have broad application prospects in the fields of flexible photovoltaic devices and photovoltaic building integration.
[0003] Whether it is a crystalline silicon solar cell or a thin-film solar cell, in order to improve the absorption rate of sunlight, it is necessary to prepare an anti-reflection structure on the surface of the cell. At present, the anti-reflection structure of crystalline silicon solar cells on the market is usually a light-trapping velvet surface superimposed with SiN x Anti-reflection film. The preparation of this anti-reflection structure requires the use of alkali or acid to react with silicon to form a light-trapping structure to reduce the reflection loss of incident sunlight. Based on the different densities of the atomic arrangement of single-crystalline silicon, alkali can anisotropically etch it to form a positive-inverted pyramid structure composed of the {111} crystal plane family, which has a better light-trapping effect. However, due to the surface saw marks and irregularities of the crystal phase, it is impossible to etch a uniform anti-reflection structure with alkali in diamond wire-cut polycrystalline silicon. Usually, acid is used to etch pits to enhance the light-trapping effect. The texturing process has two prominent disadvantages: (1) the large-scale use of alkali or acid corrosion will cause silicon wafer loss, and the waste liquid treatment will increase production costs and is not environmentally friendly; (2) The etched light-trapping structure will increase the specific surface area of the silicon wafer, resulting in more serious Auger recombination and reduced short-circuit current. It is even more difficult to prepare a velvet surface for thin-film solar cells.
[0004] In view of the above problems, the traditional texturing process is placed on SiN plating x Or after the transparent conductive oxide anti-reflection film, the texturing method uses soft nanoimprinting to replace the acid-base etching method, which is an effective way to overcome the shortcomings of corrosion texturing and give solar cells better anti-reflection effect. Moreover, the anti-reflection structure is constructed outside the anti-reflection film without being restricted by corrosion, so it can be more complex and efficient than the traditional pyramid anti-reflection structure. As a convenient and inexpensive non-photolithography pattern transfer technology, soft nanoimprinting can be used to construct surfaces of different morphologies to reduce reflectivity, such as positive-inverted nanocones, nanopillars, positive-inverted pyramids, positive-inverted moth eyes, nano-thorns, etc. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects in the prior art and improve the photoelectric conversion efficiency of various types of solar cells. Specifically, a micro-nano texture anti-reflection structure for solar cells and a preparation method thereof are provided.
[0006] The specific technical solutions adopted by the present invention are as follows:
[0007] In the first aspect, the present invention provides a micro-nano texture anti-reflection structure for solar cells, wherein the solar cell is a single crystal silicon, polycrystalline silicon or thin film solar cell, and the micro-nano texture anti-reflection structure is formed by uniformly covering a texture anti-reflection layer on a flat anti-reflection film of the solar cell, and the texture anti-reflection layer has a micron-level light trapping structure or a nano-level light trapping structure or a micro-nano composite light trapping structure, and the material is polyurethane with a refractive index of 1.6 to 2.0.
[0008] As a preferred embodiment of the first aspect, the micron light-trapping structure is a positive (i.e. convex) or inverted (i.e. concave) lace cone, pyramid structure, cone structure, truncated cone structure and moth-eye structure, with a size of 1 to 5 microns; the nano light-trapping structure includes a positive (i.e. convex) or inverted (i.e. concave) nano cone, nano needle, nano column, nano pyramid and moth-eye structure, with a size of 10 to 1000 nanometers. As a preferred embodiment of the first aspect, the textured anti-reflection layer has a micron-level light-trapping structure, and the morphology of the light-trapping structure is preferably a lace inverted cone; the lace inverted cone is a depression in the form of an inverted cone, and the side of the concave cone has concave-convex wrinkles, and the outer edge of the cone cross section is lace.
[0009] As a preferred embodiment of the first aspect, the solar cell is preferably a double-sided crystalline silicon solar cell, wherein the anti-reflection film is SiN x Anti-reflection film.
[0010] In a second aspect, the present invention provides a method for preparing a micro-nano texture anti-reflection structure for a solar cell according to the first aspect, which is specifically as follows:
[0011] S1: dissolving triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane in analytical pure ethanol, and adjusting the pH value to 4-5 with dilute hydrochloric acid to obtain an anti-sticking solution; immersing a hard template with a concave or convex texture structure on the surface into the anti-sticking solution for anti-sticking treatment;
[0012] S2: The main agent and curing agent of Dow Corning DC184 are fully stirred and mixed, and then vacuum degassing is performed to obtain a Dow Corning DC184 mixture; the Dow Corning DC184 mixture is dripped onto the hard template after the anti-sticking treatment in S1, and vacuum degassing is performed again, and a polydimethylsiloxane soft template with a texture structure is obtained after the first thermal curing; the polydimethylsiloxane soft template is immersed in the anti-sticking solution in S1 for anti-sticking treatment;
[0013] S3: mixing isocyanate, thiol and dibutyltin dichloride in an ice bath, stirring evenly and then degassing in vacuum to obtain a polyurethane mixed solution;
[0014] S4: The polyurethane mixed solution is evenly covered on the flat anti-reflection layer surface of the solar cell, and the polydimethylsiloxane soft template after the anti-sticking treatment in S2 is imprinted on the surface of the polyurethane mixed solution and pressure is applied. After the second thermal curing, the polydimethylsiloxane soft template is peeled off to form a textured anti-reflection layer with a texture structure on the anti-reflection layer, thereby obtaining a micro-nano textured anti-reflection structure.
[0015] As a preferred embodiment of the above-mentioned second aspect, preferably, the mass fraction of the triethoxy-1H,1H,2H,2H-tridecafluorooctylsilane described in S1 in ethanol is 0.1wt% to 1wt%; preferably, the hard template described in S1 is an inorganic material hard template of an anodic aluminum oxide AAO template, a silicon template or a metal template with a micro-nano texture structure morphology, or a polyurethane or epoxy resin organic material hard template transferred from the inorganic material hard template; further preferably, the hard template is an AAO hard template with evenly distributed inverted cone depression structures, and the diameter and height of the inverted cone depression structures are 450nm and 1500nm, respectively.
[0016] As a preferred embodiment of the second aspect, preferably, the mass ratio of the main agent to the curing agent in the Dow Corning DC184 mixture described in S2 is 10:1; preferably, the first thermal curing temperature described in S2 is 60-80°C, and the thermal curing time is 3-8h.
[0017] As a preference for the above-mentioned second aspect, preferably, the functional group ratio of the isocyanate and the thiol described in S3 is 1:1; preferably, the isocyanate is toluene diisocyanate or meta-xylyl diisocyanate; preferably, the thiol is 4-mercaptomethyl-3,6-dithia-1,8-octanedithiol or 1,4-benzenedithiol; preferably, the concentration of dibutyltin dichloride in the polyurethane mixed solution is 100-200 ppm.
[0018] As a preference for the above-mentioned second aspect, preferably, the coating described in S4 is performed by spin coating, scraper coating, spray coating, pulling or roller coating, and further preferably by spin coating or scraper coating; preferably, the pressure applied in S4 is 0.01 to 1 MPa; preferably, the second thermal curing temperature is 110 to 130°C, and the thermal curing time is 1 to 4 hours.
[0019] In a third aspect, the present invention provides a micro-nano texture anti-reflection structure for solar cells obtained by any preparation method described in the second aspect above.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The micro-nano texture anti-reflection structure obtained by the preparation method provided by the present invention can be applied to various types of solar cells and can achieve significant anti-reflection effects in a wide band, thereby effectively improving the photoelectric conversion efficiency of solar cells.
[0022] (2) The preparation method provided by the present invention can conveniently prepare various customized structures by changing the hard template morphology without the need for photolithography and etching. The preparation method is low in cost, environmentally friendly and simple, can be superimposed on the completed solar cell sheet, is compatible with existing processes, and has commercial potential; BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a schematic diagram of the anti-reflection structure prepared in Example 1;
[0024] Figure 2 This is a SEM image of the surface of the anti-reflection structure prepared in Example 1;
[0025] Figure 3 This is a comparison chart of the reflectivity of the cell with the anti-reflection structure prepared in Example 1 and the original cell;
[0026] Figure 4 is a schematic diagram of the anti-reflection structure prepared in Example 2;
[0027] Figure 5 This is a comparison chart of the reflectivity of the cell with an anti-reflection structure prepared in Example 2 and the original cell;
[0028] Figure 6 Schematic diagram of the anti-reflection structure prepared in Example 3;
[0029] Figure 7 This is a comparison chart of the reflectivity of the cell with an anti-reflection structure prepared in Example 3 and the original cell;
[0030] Figure 8 This is a comparison chart of the external quantum efficiency and integrated current of the cell with anti-reflection structure prepared in Example 1 and the original cell. DETAILED DESCRIPTION
[0031] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0032] The micro-nano texture anti-reflection structure provided by the present invention can be applied to a surface coated with SiN xCrystalline silicon solar cells with anti-reflection film or transparent conductive oxide film and screen-printed metal grid lines can replace the positive pyramid velvet used in the industry, and can also be applied to thin-film solar cells with transparent conductive oxide on the surface to make up for the disadvantage of difficult preparation of light-trapping velvet. They are compatible with existing cell preparation processes and can significantly reduce the reflectivity of solar cells in the wide visible light spectrum.
[0033] In the micro-nano texture anti-reflection structure for solar cells involved in the present invention, the solar cells can be single crystal silicon, polycrystalline silicon or various thin film solar cells, wherein the micro-nano texture anti-reflection structure is formed by uniformly covering the flat anti-reflection film of the solar cell with a texture anti-reflection layer. The anti-reflection film of the solar cell depends on the type of solar cell, and can be an ITO anti-reflection film or a SiN x Anti-reflection film: The textured anti-reflection layer is covered on the anti-reflection film, and the textured anti-reflection layer has a micron-scale light trapping structure (size is 1 to 5 microns) or a nano-scale light trapping structure (size is 10 to 1000 nanometers) or a composite structure of the two.
[0034] The material used for the anti-reflection structure prepared on the surface of the solar cell of the present invention is high-refractive-index polyurethane. By selecting different isocyanate and thiol monomers, the refractive index can be freely adjusted between 1.6 and 2.0. The present invention can select hard templates with different surface structures, and can prepare a polyurethane anti-reflection film corresponding to the hard template by transfer printing of polydimethylsiloxane (PDMS) soft template. The transfer process needs to pay attention to anti-sticking treatment.
[0035] The light-trapping structure on the anti-reflection film provided by the present invention includes a micron light-trapping structure, a nano light-trapping structure and a micro-nano composite light-trapping structure, wherein the micron light-trapping structure includes a positive (i.e. convex) or inverted (i.e. concave) lace cone, pyramid structure, cone structure, truncated cone structure and moth-eye structure, with a size of 1 to 5 microns; the nano light-trapping structure includes a positive (i.e. convex) or inverted (i.e. concave) nano cone, nano needle, nano column, nano pyramid and moth-eye structure, with a size of 10 to 1000 nanometers. However, it should be noted that the light-trapping structure in the present invention is limited by factors such as processing technology and processing errors during actual processing, and does not necessarily form the above-mentioned completely standard geometric shape. There may be certain deviations, but these deviations will not essentially affect the effect of the final light-trapping structure.
[0036] The specific preparation method of the above-mentioned micro-nano texture anti-reflection structure and the corresponding technical effects are described below through several embodiments. However, it should be noted that the following embodiments are further explanations of the principles and features of the present invention, but the scope of the invention is not limited thereto.
[0037] Example 1
[0038] This embodiment provides a method for preparing a micro-nano texture anti-reflection structure using an anodic aluminum oxide AAO hard template with an inverted cone structure. The specific preparation steps are as follows:
[0039] (1) Anti-sticking treatment of hard template: triethoxy-1H,1H,2H,2H-tridecafluorooctylsilane was dissolved in analytical pure ethanol to obtain a mixed solution with a mass percentage of 0.5wt%, and the pH value was adjusted to 4-5 with dilute hydrochloric acid. After stirring for 10 minutes, an anti-sticking solution was obtained; an AAO hard template with an inverted cone structure uniformly distributed on the surface (the inverted cone structure is a conical concave structure with a size of 450nm in diameter and 1500nm in height) was immersed in the anti-sticking solution for 10 minutes, taken out, ultrasonically cleaned with deionized water, and placed in an oven for drying.
[0040] (2) Preparation of PDMS soft template: Weigh 0.5 g and 0.05 g of Dow Corning DC184 main agent and curing agent respectively, stir and mix them in a mass ratio of main agent: curing agent = 10:1, put them in a vacuum drying oven to degas for 30 min at room temperature to obtain a Dow Corning DC184 mixture; drip the Dow Corning DC184 mixture onto the above-mentioned inverted cone structure AAO hard template that has been treated with anti-sticking treatment, degasse again in vacuum, perform the first thermal curing at 80°C for 4 h, peel off the PDMS, and the right cones will undergo regional agglomeration to obtain a PDMS soft template with a lace right cone morphology; immerse the above-mentioned PDMS soft template in the anti-sticking solution for 10 min, take it out, ultrasonically clean it with deionized water, and put it in an oven to dry.
[0041] (3) Preparation of polyurethane solution: Since the content of dibutyltin dichloride in the small-dose experiment is very small, in order to ensure the uniformity of the mixing of the reagents, 2 mg of dibutyltin dichloride was first dissolved in 1 g of m-phenylenediisocyanate and stirred at room temperature for 10 min to obtain a mixed solution. Subsequently, 0.2 g of the above mixed solution was added to 1.19 g of m-phenylenediisocyanate in an ice bath state and stirred for 10 min. Then, 1.28 g of 4-mercaptomethyl-3,6-dithia-1,8-octanedithiol was added and stirred for 5 min. The mixture was placed in a vacuum drying oven for degassing for 30 min to obtain an uncured polyurethane mixed solution, wherein the molar ratio of 4-mercaptomethyl-3,6-dithia-1,8-octanedithiol:m-phenylenediisocyanate is 2:3.
[0042] (4) Preparation of polyurethane anti-reflection structure: The back of the bifacial PERC cell is used as the imprint substrate, and the outermost layer is SiN x Anti-reflection film and printed aluminum grid lines. xThe polyurethane mixed solution was evenly spin-coated on the surface of the anti-reflection film at a spin-coating speed of 1000 r / min. After 10 seconds, the PDMS soft template treated with anti-sticking was imprinted on the surface of the polyurethane mixed solution, and a pressure of 0.02 MPa was applied to fully infiltrate it. After a second thermal curing at 120°C for 2 hours, the PDMS soft template was peeled off to obtain a textured anti-reflection layer, thereby SiN x The anti-reflection film and the textured anti-reflection layer are combined to form a polyurethane anti-reflection structure with a lace inverted cone morphology and a light-trapping structure.
[0043] The schematic diagram of the polyurethane anti-reflection structure provided in this embodiment is as follows Figure 1 The specific electron microscope image of the textured anti-reflection layer is shown in Figure 2 As shown, it can be seen that its surface has a light-trapping structure with a micron-scale lace inverted cone morphology.
[0044] In order to verify the effect of the anti-reflection structure prepared in this example on the performance of the solar cell, the reflectance spectrum of the structure was compared with that of the original cell (i.e., the bifacial PERC cell). Figure 3 As shown, it can be clearly found that after a layer of polyurethane anti-reflection structure with a lace inverted cone morphology is superimposed on the back of the double-sided PERC cell in this embodiment, the anti-reflection effect in a wide visible light band is substantially improved.
[0045] Example 2
[0046] This embodiment provides a method for preparing a micro-nano texture anti-reflection structure using an inverted moth-eye structure anodized aluminum oxide AAO hard template, and the specific preparation steps are as follows:
[0047] (1) Anti-sticking treatment of hard template: triethoxy-1H,1H,2H,2H-tridecafluorooctylsilane was dissolved in analytical pure ethanol to obtain a mixed solution with a mass percentage of 0.5wt%, and the pH value was adjusted to 4-5 with dilute hydrochloric acid. After stirring for 10 minutes, an anti-sticking solution was obtained; an AAO hard template with an inverted moth-eye structure evenly distributed on the surface (the inverted moth-eye structure is a depression in the form of an inverted moth-eye, with a size of: bottom diameter 100nm, top diameter 450nm, height 400nm) was immersed in the anti-sticking solution for 10 minutes, taken out, ultrasonically cleaned with deionized water, and placed in an oven for drying.
[0048] (2) Preparation of PDMS soft template: Weigh 0.5 g and 0.05 g of Dow Corning DC184 main agent and curing agent respectively, stir and mix them in a mass ratio of main agent: curing agent = 10:1, put them in a vacuum drying oven for degassing at room temperature for 30 min to obtain a Dow Corning DC184 mixture; drip the Dow Corning DC184 mixture onto the above-mentioned AAO hard template with inverted moth-eye structure that has been subjected to anti-sticking treatment, degasse again in vacuum, perform the first thermal curing at 80°C for 4 h, peel off the PDMS, and obtain a PDMS soft template with a positive moth-eye morphology; immerse the above-mentioned PDMS soft template in the anti-sticking solution for 10 min, take it out, ultrasonically clean it with deionized water, and put it in an oven to dry.
[0049] (3) Preparation of polyurethane solution: Since the content of dibutyltin dichloride in the small-dose experiment is very small, in order to ensure the uniformity of the mixing of the reagents, 2 mg of dibutyltin dichloride was first dissolved in 1 g of m-phenylenediisocyanate and stirred at room temperature for 10 min to obtain a mixed solution. Subsequently, 0.2 g of the above mixed solution was added to 1.19 g of m-phenylenediisocyanate in an ice bath state and stirred for 10 min. Then, 1.28 g of 4-mercaptomethyl-3,6-dithia-1,8-octanedithiol was added and stirred for 5 min. The mixture was placed in a vacuum drying oven for degassing for 30 min to obtain an uncured polyurethane mixed solution, wherein the molar ratio of 4-mercaptomethyl-3,6-dithia-1,8-octanedithiol:m-phenylenediisocyanate is 2:3.
[0050] (4) Preparation of polyurethane anti-reflection structure: The back of the bifacial PERC cell is used as the imprint substrate, and the outermost layer is SiN x Anti-reflection film and printed aluminum grid lines. x The polyurethane mixed solution was evenly spin-coated on the surface of the anti-reflection film at a spin-coating speed of 1000 r / min. After 10 seconds, the PDMS soft template treated with anti-sticking was imprinted on the surface of the polyurethane mixed solution, and a pressure of 0.02 MPa was applied to fully infiltrate it. After a second thermal curing at 120°C for 2 hours, the PDMS soft template was peeled off to obtain a textured anti-reflection layer, thereby SiN x The anti-reflection film and the textured anti-reflection layer are combined to form a polyurethane anti-reflection structure with an inverted moth-eye morphology.
[0051] The cross-sectional schematic diagram of the polyurethane anti-reflection structure provided in this embodiment is as follows Figure 4 As shown, in order to verify the effect of the inverted moth-eye morphology polyurethane anti-reflection structure prepared in this embodiment on the performance of solar cells, the reflectance spectrum of the structure was compared with that of the original cell surface (i.e., bifacial PERC cell). The results are shown in FIG. Figure 5As shown, it can be clearly found that after a layer of inverted moth-eye morphology polyurethane anti-reflection structure is superimposed on the back of the double-sided PERC cell in this embodiment, the anti-reflection effect in a wide visible light band is substantially improved.
[0052] Example 3
[0053] This embodiment provides a method for obtaining a positive moth-eye structure epoxy resin hard template by transferring an anodized aluminum oxide AAO hard template with an inverted moth-eye structure using epoxy resin, and using the template to prepare a micro-nano texture anti-reflection structure. The specific preparation steps are as follows:
[0054] (1) Anti-sticking treatment of hard template: triethoxy-1H,1H,2H,2H-tridecafluorooctylsilane was dissolved in analytical pure ethanol to obtain a mixed solution with a mass percentage of 0.5wt%, and the pH value was adjusted to 4-5 with dilute hydrochloric acid. After stirring for 10 minutes, an anti-sticking solution was obtained; an AAO hard template with an inverted moth-eye structure evenly distributed on the surface (the inverted moth-eye structure is a depression in the form of an inverted moth-eye, with a size of: bottom diameter 100nm, top diameter 450nm, height 900nm) was immersed in the anti-sticking solution for 10 minutes, taken out, ultrasonically cleaned with deionized water, and placed in an oven for drying.
[0055] (2) Preparation of epoxy resin hard template: Weigh 0.6g and 0.2g of epoxy resin AB crystal glue respectively, stir and mix them according to the mass ratio of main agent: curing agent = 3:1, put them in a vacuum drying oven to degas for 30 minutes at room temperature, and then drip the mixed solution onto the AAO hard template with an inverted cone structure that has been treated with anti-sticking. After vacuum degassing again, heat cure at 60°C for 3 hours to peel off the epoxy resin to obtain an epoxy resin hard template with a positive moth-eye morphology on the surface; immerse the epoxy resin hard template in the anti-sticking solution for 10 minutes, take it out, ultrasonically clean it with deionized water, and put it in an oven to dry.
[0056] (3) Preparation of PDMS soft template: Weigh 0.5 g and 0.05 g of Dow Corning DC184 main agent and curing agent respectively, stir and mix them in a mass ratio of main agent: curing agent = 10:1, put them in a vacuum drying oven for degassing at room temperature for 30 minutes to obtain a Dow Corning DC184 mixture; drip the Dow Corning DC184 mixture onto the above-mentioned epoxy resin hard template with positive moth-eye morphology that has been subjected to anti-sticking treatment, degasse again in vacuum, perform the first thermal curing at 60°C for 8 hours, peel off the PDMS, and obtain a PDMS soft template with inverted moth-eye morphology; immerse the above-mentioned PDMS soft template with inverted moth-eye morphology in the anti-sticking solution for 10 minutes, take out, ultrasonically clean it with deionized water, and put it in an oven to dry.
[0057] (4) Preparation of polyurethane solution: Since the content of dibutyltin dichloride in the small-dose experiment is very small, in order to ensure the uniformity of the mixing of the reagents, 2 mg of dibutyltin dichloride was first dissolved in 1 g of m-phenylenediisocyanate and stirred at room temperature for 10 min to obtain a mixed solution. Subsequently, 0.2 g of the above mixed solution was added to 1.19 g of m-phenylenediisocyanate in an ice bath state and stirred for 10 min. Then, 1.28 g of 4-mercaptomethyl-3,6-dithia-1,8-octanedithiol was added and stirred for 5 min. The mixture was placed in a vacuum drying oven for degassing for 30 min to obtain an uncured polyurethane mixed solution, wherein the molar ratio of 4-mercaptomethyl-3,6-dithia-1,8-octanedithiol:m-phenylenediisocyanate is 2:3.
[0058] (5) Preparation of polyurethane anti-reflection structure: The front side of the bifacial PERC cell is used as the imprint substrate, which is alkaline polished and the outermost layer is coated with SiN x Anti-reflection coating. SiN in solar cells x The polyurethane mixed solution was evenly spin-coated on the surface of the anti-reflection film at a spin-coating speed of 1000 r / min. After 10 seconds, the PDMS soft template treated with anti-sticking was imprinted on the surface of the polyurethane mixed solution, and a pressure of 0.02 MPa was applied to fully infiltrate it. After a second thermal curing at 120°C for 2 hours, the PDMS soft template was peeled off to obtain a textured anti-reflection layer, thereby SiN x The anti-reflection film and the textured anti-reflection layer are combined to form a polyurethane anti-reflection structure with a positive moth-eye morphology.
[0059] The cross-sectional schematic diagram of the polyurethane anti-reflection structure provided in this embodiment is as follows Figure 6 As shown, in order to verify the effect of the anti-reflection structure prepared in this embodiment on the performance of the solar cell, the reflection spectrum of its surface was tested and compared with the original cell (i.e., bifacial PERC cell). The results are as follows Figure 7 As shown, it can be clearly found that after a layer of polyurethane anti-reflection structure with a positive moth-eye morphology is superimposed on the polished front side of the double-sided PERC cell in this embodiment, the anti-reflection effect in a wide visible light band is substantially improved.
[0060] The surface reflectivity of the solar cells with micro-nano texture anti-reflection structures prepared in the above three embodiments is significantly reduced in the visible light band. By comparison, it can be seen that the anti-reflection effect of the lace inverted cone structure in Example 1 is better than that of the inverted moth-eye structure in Example 2 and the positive moth-eye structure in Example 3.
[0061] The improvement of anti-reflection effect will increase the absorption of light by solar cells, thereby generating a gain in the short-circuit current of the cell. Taking Example 1 as an example, a comparison of the external quantum efficiency and integrated current of a solar cell with a lace inverted cone and an original cell is shown in the figure below. Figure 8As shown, it can be clearly seen that the micro-nano texture anti-reflection structure improves the integrated current of the battery, which will also improve the photoelectric conversion efficiency of the solar cell.
[0062] The micro-nano texture anti-reflection structure prepared by the present invention is located on the outside of the battery cell electrode and can be superimposed on the existing battery preparation process. Moreover, the preparation method of the anti-reflection structure can arbitrarily adjust its micro-nano texture structure by changing the morphology of the original hard template. The preparation method is low in cost, environmentally friendly and simple. Therefore, the present invention has good application prospects for improving the anti-reflection of existing solar cells.
[0063] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for preparing a micro-nano texture anti-reflection structure for solar cells, characterized in that: The details are as follows: S1: dissolving triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane in analytical pure ethanol, and adjusting the pH value to 4-5 with dilute hydrochloric acid to obtain an anti-sticking solution; immersing a hard template with a concave or convex texture structure on the surface into the anti-sticking solution for anti-sticking treatment; S2: The main agent and curing agent of Dow Corning DC184 are fully stirred and mixed, and then vacuum degassing is performed to obtain a Dow Corning DC184 mixture; the Dow Corning DC184 mixture is dripped onto the hard template after the anti-sticking treatment in S1, and vacuum degassing is performed again, and a polydimethylsiloxane soft template with a texture structure is obtained after the first thermal curing; the polydimethylsiloxane soft template is immersed in the anti-sticking solution in S1 for anti-sticking treatment; S3: mixing isocyanate, thiol and dibutyltin dichloride in an ice bath, stirring evenly and then degassing in vacuum to obtain a polyurethane mixed solution; S4: uniformly covering the polyurethane mixed solution on the flat anti-reflection layer surface of the solar cell, and imprinting the polydimethylsiloxane soft template after the anti-sticking treatment in S2 on the surface of the polyurethane mixed solution and applying pressure, and removing the polydimethylsiloxane soft template after the second thermal curing, forming a textured anti-reflection layer with a texture structure on the anti-reflection layer, thereby obtaining a micro-nano textured anti-reflection structure; The solar cell is a double-sided crystalline silicon solar cell, wherein the anti-reflection film is SiN x Anti-reflection film.
2. The preparation method according to claim 1, characterized in that The mass fraction of triethoxy-1H,1H,2H,2H-tridecafluorooctylsilane described in S1 in ethanol is 0.1 wt%~1 wt%; the hard template described in S1 is an inorganic material hard template of an anodic aluminum oxide AAO template, a silicon template or a metal template with a micro-nano texture structure morphology, or a polyurethane or epoxy resin organic material hard template transferred from the inorganic material hard template.
3. The preparation method according to claim 1, characterized in that The hard template is an AAO hard template with inverted cone recessed structures evenly distributed, and the diameter and height of the inverted cone recessed structures are 450 nm and 1500 nm respectively.
4. The preparation method according to claim 1, characterized in that The mass ratio of the main agent to the curing agent in the Dow Corning DC184 mixture described in S2 is 10:1; the first heat curing temperature described in S2 is 60~80℃, and the heat curing time is 3~8h.
5. The preparation method according to claim 1, characterized in that The functional group ratio of the isocyanate and the thiol described in S3 is 1:1; the isocyanate is toluene diisocyanate or m-xylyl diisocyanate; the thiol is 4-mercaptomethyl-3,6-dithia-1,8-octanedithiol or 1,4-benzenedithiol; and the concentration of dibutyltin dichloride in the polyurethane mixed solution is 100~200 ppm.
6. The preparation method according to claim 1, characterized in that The polyurethane mixed solution described in S4 is covered on the flat anti-reflection layer surface of the solar cell by spin coating, scraper coating, spray coating, pulling or roller coating; the pressure applied in S4 is 0.01~1 Mpa; the second thermal curing temperature is 110~130℃, and the thermal curing time is 1~4 h.
7. The preparation method according to claim 6, characterized in that: The polyurethane mixed solution described in S4 is coated on the flat anti-reflection layer surface of the solar cell by spin coating or scraping.
8. A micro-nano texture anti-reflection structure for solar cells obtained according to the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Smooth crystalline silicon-light trapping film composite solar cell
CN103236447A
Solar cell component and manufacturing method thereof
CN103579389A
Method for producing structured surfaces
CN108137310A